Screening of Natural Antivirals Against the COVID-19 Pandemic- A Compilation of Updates - De, Baishakhi; Goswami, Tridib K.; Raghavan, Vijaya G.S. (Current Traditional Medicine, 2023)
Coronavirus disease 2019 (COVID-19), named by WHO, is a real public health disaster of the third millennium. This highly contagious viral disease has infected the world population and is now a global pandemic. This acute respiratory distress syndrome (ARDS) has severe complications like pneumonitis, respiratory failure, shock, multiorgan failure, and death. Well-defined FDAapproved synthetic is not yet available. Case management strategies like lockdown, use of masks and sanitizers, social distancing, and repurposing of antiviral drugs were initially undertaken to cope with this pandemic. Different broad-spectrum antiviral drugs are being repurposed as one of the treatment modalities. The global vaccination programme with the newly launched COVID-19 vaccines, Covishield, covaxin, sputnik V, etc., is an ongoing process. Simultaneously, significant research is being carried out in search of natural antivirals and evaluating the potency of food bioactives to aid naturistic protection against the coronavirus. This mini-review has compiled the latest updates on the screening and evidence-based mechanistic evaluation of phytochemicals and food bioactives as non-pharmacological adjuvant aid in COVID pandemics.
Keywords: Coronavirus